KARAKTERISASI FISIK PATI GANYONG (Canna edulis Kerr) TERMODIFIKASI SECARA HIDROTERMAL - Maila Yesti Kuswandari; Olivia Anastria; Dyah Hesti Wardhani (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2013)
Canna starch are a roots which abundant in Indonesia. Canna starch has the potential to be developed because it has many uses, especially potential to be used as a functional food ingredients, for example as sources of carbohydrates that used as intermediate products (such as noodles, vermicelli, biscuit etc). Modification of Canna starch change the functional properties of the starch  to increase the added value as a functional food ingredient.. The aim of this research was to study the effect of temperature and heating time on the physical properties of hydrothermally modified canna starches.Heat treatment modifies heating of starch at elevated temperature(100oC, 110oC) in varying moisture level for certain period (2, 4, 6 hour). The results show that the analysis bulk density(0,6692-0,7528 gr/ml), solid density(0,7588-0,8396 gr/ml) have a higher value than native canna starch. While the analysis of the water content of wet weight(8-14%) in the modified starch have a lower value than native starch.Advantages of heat moisture treatment modification change the functional properties to be better.